Analisis Keberhasilan Pemasaran Produk Agribisnis Berbasis Instagram di Provinsi Bali - Widiarta, Ketut Trisna Thana; Ustriyana, I Nyoman Gede; Arisena, Gede Mekse Korri (Nandur, 2021)
Instagram is one type of e-commerce website that is used to sell products or services digitally with Instagram being the 4th most active platform on social media. “This study aims to analyze the characteristics of” agribusiness businesses using Instagram using qualitative descriptive with simple tabulations, analyzing the quality of Instagram, the use of Instagram and usage satisfaction in agribusiness businesses by using descriptive analysis to explain how the perspectives of SME on their Instagram and analyze the influence of Instagram quality, Instagram usage. and satisfaction with the use of successful e-commerce businesses in Bali Province “using the Structural Equation Modeling-Partial Least Square (SEM-PLS) approach.” The research sample was 31 SME selling vegetables, fruits and meat using Instagram and using the hashtags #sayurbali, #buahbali and #dagingbali. The results show that most of the Instagram-based SME have an age of 26-30 years old SME with undergraduate education levels and Instagram contributing 50% -75% increase in sales. In addition, it was found that Instagram was able to increase SME sales results by “paying attention to the quality of “Instagram, the use of Instagram, usage satisfaction and the success of e-commerce. Instagram quality, Instagram usage and usage satisfaction indicate a significant positive influence on the success of e-commerce as evidenced by each variable having a value of 3.961; 2,067 and 2,002 for the success of e-commerce.